Consumer-driven media planning and buying. Issue 8 (17th November 2018) - Schultz, Don E.; Block, Martin P.; Viswanathan, Vijay
Abstract: Media planning and buying has historically focused on efficient message distribution. Thus, most media planning approaches have focused on optimization models based on estimated reach and frequency. Those models assumed a hierarchy of effects base where consumers move through a purchasing journey driven by assumed media exposures. In this exploratory paper, an argument is made for a consumer-generated media consumption model. Thus, their focus is on media influence rather than simply exposures. The model is demonstrated with data from a US-based online consumer data-set. The authors posit technology has made their approach superior to traditional models. A set of managerial implications is included.